Brazilian studies in philosophy and history of science an account of recent works - Krause, Décio; Videira, Antônio Augusto Passos (Boston studies in the philosophy of science, 2011)
This volume, "The Brazilian Studies in the Philosophy and History of Science", is the first attempt to present to a general audience, works from Brazil on this subject.